Influence of Drying on the Properties of Pears of the Rocha Variety (Pyrus communis L.). - Santos, Sandra (2015)
Rocha pear (Pyrus communis L.) is the main cultivar produced in Portugal, usually consumed in fresh. However, the drying of the pear can be an oppor- tunity for development and enables the provision of alternative products to consumers. This work evaluates the effect of drying on some chemical and physical properties of pears of the Rocha variety. Furthermore, the origin of the pears was also a variable studied. For the completion of this work, pears from five different locations were analysed in fresh and after convective air drying at two different temperatures, 40 and 60°C. The properties analysed were dimensions of pears in terms of height and diameter, total solids content, acidity, maturation index, processing yields, colour and textural attributes. The results showed that the peel had lower acidity and higher maturation index, when compared to the pulp and that drying greatly reduced acidity, either in the pulp or in the peel. However, this variation was not influenced by the drying temperature. With respect to colour, total colour differences between 25 and 50 were observed (for the dried pears in relation to the fresh) and in this case increasing the drying temperature caused evident variations in the peel but not in the pulp. As to the textural attributes, hardness and chewiness were the ones that showed the higher changes with drying, increasing considerably with drying temperature.